Alcohol dependency, recovery, and social words. Issue 4 (8th March 2013) - Szabó, József; Gerevich, József
Abstract The influence of social support to recovery is a well‐known phenomenon. We supposed that examining relapsed and recovered alcohol‐dependent patients' autobiography vocabularies we could detect special differences. First, we examined group of relapsed patients treated in hospital at least twice within a year (n = 30). We chose for at least 2 year abstinent persons into the second group (n = 20). We compared their autobiographies by the Atlas.ti 5.0 content analyzing software and detected higher frequency of social words referring to social connections and social activity in the recovered patients' groups. The chi‐square test showed significant difference (p = 0.000155 < 0.01) between the frequency of social words of the two groups. We could estimate the spontaneous indicators of their social support via the content analysis.